Assessment of Perceived Role of Emerging Technologies in Social Studies Teaching and Evaluation Strategies among Secondary Schools in Ife East, Osun State Akinwande, A. E. - Akinwande, Adeyoola Eunice (Kashere Journal of Education, 2025)
This study assessed the perceived role of emerging technologies in Social Studies teaching and evaluation strategies among secondary schools in Ife East, Osun State. The specific objectives of the study were to determine the role of emerging technology in Social Studies and determine the role of emerging technology in evaluation strategies. It adopted the survey research design; three public junior secondary schools in the Ife East Local Government Area of Osun State were randomly selected, and a total of 150 JSS II students (46 males and 104 females) participated in the study. Two experts validated the instruments. Two research instruments: Role of Technology in Social Studies (r = 0.76) and Emerging Technology Scale (r = 0.81) were administered to students. Data were analysed using descriptive statistics (frequency count, percentage, mean, and standard deviation). Findings of the study revealed the weighted mean of 2.63 out of the 4.00 maximum obtainable scores, which is higher than the standard mean of 2.50. the role of emerging technology in Social Studies was very positive. Additionally, the weighted mean of 2.63 out of the 4.00 maximum attainable scores surpasses the standard mean of 2.50. The role of emerging technologies in evaluation strategies was very positive. The study established that emerging technologies contribute significantly to more efficient and transparent assessment practices. Based on the findings of this study, it was recommended that government and school administrators should provide reliable internet access, updated digital devices, computer laboratories, and multimedia equipment to support meaningful use of emerging technologies in Social Studies classrooms. We should organise regular training programmes, workshops, and in-service courses to update teachers’ skills in digital pedagogy, instructional design, and technology-assisted evaluation strategies. Curriculum planners at national and state levels should incorporate the use of digital tools, such as GIS, VR/AR, AI-based platforms, and interactive multimedia, into Social Studies curriculum content and learning outcomes.